The Idealism Development Of the Main Character In Oil! Novel - Muhammad Nush Imam Muttaqien (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
This term paper aims to identify Bunny, the main characters idealism through the social class theory based on the World War background. The objective of this research is identify, analyze, and describe the development of the main characters idealism and the factor that affect the development. The method that this researh used are qualitative and decriptive analysis through the intrinsik elements approach. The result of this research show that Bunnys idealism can develop from the idealism that close to the kapitalism class because of his father teaching to the idealism that supporting the proletarian class. This research also found the factor that affect the development of Bunnys idealism such as other character, backgruond, plot and conflict. The fifth section contains the implications of the research represented by one sentence. The fifth part is an optional part, meaning that it may or may not be conveyed.